MODEL ASESMEN PENANGANAN KEKERASAN SEKSUAL DAN INTEGRASI KONSELING SPIRITUAL DI UIN SYARIF HIDAYATULLAH JAKARTA - Wiwi Sajaroh (Center for Gender and Child Studies (Pusat Studi Gender dan Anak) LP2M UIN Syarif Hidayatullah Jakarta, 2025)
Abstract. Sexual violence in higher education is not only an individual offence, but also an institutional problem shaped by hierarchy, stigma, and unequal power relations. This study examines how the Center for Gender and Child Studies (PSGA) at UIN Syarif Hidayatullah Jakarta operationalises its assessment model for handling sexual violence cases and how spiritual counselling is integrated into survivor rehabilitation. Using a descriptive qualitative case study, data were collected through two Focus Group Discussions, in-depth interviews, and review of PSGA service documents. Thirteen informants participated, including PSGA service managers, psychologists, spiritual counsellors, assistants, and student survivors. The findings show that PSGA applies a six-stage assessment model: initial identification, data collection, psychological assistance, legal assistance, survivor rehabilitation, and monitoring and evaluation. The model enables a more holistic response by combining psychological, legal, social, and spiritual support. Spiritual counselling contributes to recovery by helping survivors rebuild dignity, reduce self-blame, and reinterpret traumatic experiences through an inclusive and non-judgemental religious framework. However, the model remains constrained by seniority, institutional reputation, stigma, and limited long-term monitoring. The study concludes that effective handling of sexual violence in religious higher education requires systematic procedures, trauma-informed spiritual support, and firm institutional commitment to survivor protection and accountability mechanisms. Abstrak Kekerasan seksual di perguruan tinggi bukan hanya persoalan individual, tetapi juga masalah kelembagaan yang dipengaruhi oleh hierarki, stigma, dan relasi kuasa yang tidak setara. Penelitian ini mengkaji bagaimana Pusat Studi Gender dan Anak (PSGA) UIN Syarif Hidayatullah Jakarta mengoperasionalkan model asesmen penanganan kekerasan seksual serta bagaimana konseling spiritual diintegrasikan dalam rehabilitasi penyintas. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan desain studi kasus. Data dikumpulkan melalui dua sesi Focus Group Discussion, wawancara mendalam, dan telaah dokumen layanan PSGA. Sebanyak 13 informan terlibat, terdiri atas pengelola layanan, psikolog, konselor spiritual, pendamping, dan mahasiswa penyintas. Hasil penelitian menunjukkan bahwa PSGA menerapkan model asesmen enam tahap, yaitu identifikasi awal, pengumpulan data, pendampingan psikologis, pendampingan hukum, rehabilitasi penyintas, serta monitoring dan evaluasi. Model ini memungkinkan respons yang lebih holistik karena menggabungkan dukungan psikologis, hukum, sosial, dan spiritual. Konseling spiritual berkontribusi pada pemulihan dengan membantu penyintas membangun kembali martabat diri, mengurangi rasa bersalah, dan memaknai pengalaman traumatis melalui kerangka keagamaan yang inklusif dan tidak menghakimi. Namun, efektivitas model masih dibatasi oleh senioritas, reputasi institusi, stigma, dan lemahnya monitoring jangka panjang. Penelitian ini menyimpulkan bahwa penanganan kekerasan seksual di perguruan tinggi keagamaan membutuhkan prosedur sistematis, dukungan spiritual berbasis trauma-informed, serta komitmen kelembagaan terhadap perlindungan penyintas dan akuntabilitas.